Mapping evidence on educational interventions for adolescents with cancer: a scoping review protocol - Kyei-Dompim, Joana; Kuupiel, Desmond; Diji, Abigail Kusi-Amponsah; Ncama, Busisiwe Purity (BMJ open, 2025)
IntroductionAdolescents diagnosed with cancer face unique challenges that can significantly impact their physical, emotional and social well-being. Educational interventions are essential in providing these young patients with the knowledge and skills necessary to navigate their cancer journey effectively. This scoping review aims to map the existing evidence on educational interventions tailored for adolescents with cancer, identifying gaps in the literature and informing future research and practice.Methods and analysisThe review will follow a systematic scoping review as outlined by the Joanna Briggs Institute. A preliminary search was conducted in June 2024 with the PubMed database. This will be followed by a comprehensive search strategy across multiple databases, including PubMed, SCOPUS, WoS, PsycINFO, GIM and CINAHL, to identify relevant literature published in English. All types of educational interventions targeting adolescents with cancer will be included, while studies focusing on non-cancer populations or published in non-English languages will be excluded. Data extraction will be conducted by two independent reviewers using a standardised tool, and qualitative content analysis will be performed to summarise the findings. The results will be presented in tables and figures, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses: Extension for Scoping Reviews guidelines. This scoping review has been registered with Open Science Framework (https://osf.io/7p93v).Ethics and disseminationAs this scoping review will use secondary data from published literature, ethical approval is not required. The findings will be disseminated through peer-reviewed publications, conference presentations and stakeholder engagement.